(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the ecological and nutritional significance of the saxaul humpback grasshopper (Haloxylon bukri), including its life cycle, distribution, morphological characteristics, and economic potential. The Haloxylon bukri species is widespread across the desert and semi-desert regions of Uzbekistan and Central Asia, playing a vital role in maintaining ecological balance. Due to its high protein content and healthy fatty acids, this grasshopper serves as a valuable food source for both humans and animals. The article discusses its life cycle, reproductive traits, ecological role, contribution to food security, as well as its global and regional economic importance. Additionally, recommendations are provided for sustainable harvesting, ecological monitoring, and population management. Research findings demonstrate that the saxaul humpback grasshopper represents an ecologically, nutritionally, and economically important source of sustainable food.